Основа моделювання процесів розвитку кіберспорту - Гоблик Володимир; Hoblyk Vladimir; Чизмар Іван; Csizmár Iván; Chyzmar Ivan (Видавничий дім «Гельветика», 2021)
Резюме. Стаття присвячена процесу моделювання, що орієнтований на проєктування та оптимізацію течії процесів розвитку кіберспорту. У якості основи моделювання визначений пул незалежних величин, які формуються залежно від змісту типових робіт, їх вартості та параметрів дохідності. Відповідно до вищенаведеного метою статті є виділення і деталізація основи моделювання процесів розвитку різних типів кіберспортивних організацій. Відповідно до цього мають бути вирішені наступні дослідницькі завдання: виділення і деталізація основи моделювання процесів розвитку розробників/видавців цифрових ігор; виділення і деталізація основи моделювання процесів розвитку кіберспортивних арен; виділення і деталізація основи моделювання процесів розвитку кіберспортивних клубів, тренувальних баз, буткемпів. Основа моделювання полегшить розробку підходу до моделювання системогенезу функціональних систем та онтогенезу їх розвитку для кіберспортивних організацій засобами динамічного програмування.

Abstract. The article is devoted to the modeling process, oriented on the design and optimization of the flow of processes of develop-ment of cybersport. The basis of the simulation is defined as a pool of independent values, which are formed depending on the content of typical works, their cost, and the parameters of profitability. According to the above provisions, the purpose of the article is to highlight and detail the basis of modeling the development processes of different types of cybersports organizations. Accordingly, the following research tasks should be carried out: To highlight and detail the basis for modeling the development processes of the / publishers of digital games; To highlight and detail the basis for modeling the development of cybersports arenas; highlighting and detailing the basis of modeling processes of development of cybersports clubs, training bases, boot camps. The research used an abstract and logical method that allowed theoretical aspects of the development of cybersport. The system-structure method is used to define the basis of the simulation (the specification of independent values is formed depending on the content of typical works, their cost, and profitability parameters). Based on the information provided, it is stated that: the presented independent values of production systems of cybersport on the content of analytical records of finding arguments form a reflection of the content and results of all possible transformations of data in the economic process into the final product; the resulting theoretical design will be informative enough to determine all possible variations of change by tar-get formal groups of / gaming publishers. The modeling framework will facilitate the development of a dynamic programming approach to the modeling of functional systematic analysis and development ontogeny for cybersports organizations.
Framework for process modelling cybersport development
Редакційна колегія: https://prostir.pdaba.dp.ua/index.php/journal/about/editorialTeam Зміст: https://prostir.pdaba.dp.ua/index.php/journal/issue/view/68
Keywords: кіберспортивні клуби; тренувальні бази; буткемп; розробники/видавці ігор